2002
DOI: 10.1046/j.0022-202x.2001.01694.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen- and Ultraviolet-B-Induced Signaling Pathways in Normal Human Melanocytes

Abstract: In normal human melanocytes various mitogens activate the mitogen-activated protein kinases ERK1/2 and the downstream transcription factor CREB (Ca2+/cAMP response element binding protein). Endothelin-1, basic fibroblast growth factor, and alpha-melanotropin interact synergistically to stimulate human melanocyte proliferation. The former two mitogens phosphorylated ERK1/2, its substrate p90rsk, and CREB. Alpha-melanotropin, forskolin, or dibutyryl cAMP failed to phosphorylate any of those targets, however. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 43 publications
7
85
1
Order By: Relevance
“…Treatment of human melanocytes with ET-1 activates the same MAP kinase pathway and phosphorylates CREB on Ser 133 ; these effects are enhanced in the concomitant presence of a-MSH (47,48). In human melanocytes, CREB phosphorylation is also induced by UV, in part via activation of the MAP kinase p38 (48).…”
Section: Discussionmentioning
confidence: 94%
“…Treatment of human melanocytes with ET-1 activates the same MAP kinase pathway and phosphorylates CREB on Ser 133 ; these effects are enhanced in the concomitant presence of a-MSH (47,48). In human melanocytes, CREB phosphorylation is also induced by UV, in part via activation of the MAP kinase p38 (48).…”
Section: Discussionmentioning
confidence: 94%
“…Benign nevi are located in the skin surface and are thoroughly exposed to UV-radiation and it may be speculated, therefore, that the profound JNK activation has a protective role restricting uncontrolled growth or survival of the nevus cells. Although p38 has been shown to also be activated by UV-radiation, 37 the low degree of activation in benign nevi suggests a less obvious role for this kinase in early stages of melanogenesis. In support of the differential activation of JNK and p38 in benign nevi, Vicent et al 17 recently observed activation of JNK but not p38 in normal cells of the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-talk between the NR4A Nuclear Receptor and MC1R Signaling Cascades in B16 Melanoma Cells-Although MC1R signaling functions primarily via the stimulation of adenylate cyclase resulting in the production of cAMP, emerging evidence suggests that a number of other signaling cascades are also activated by MC1R in melanocytic cells (10,41,47,48). Moreover, the NR4A subgroup has been shown to be targets of cAMP signaling in a number of cell types (25,26).…”
Section: Induction Of Nr4a Gene Expression By Mc1r Signaling In B16mentioning
confidence: 99%